The Production and Characterization of Spray Dried Tamarillo Powders - Al Mubarak, Ahmad (Auckland University of Technology, 2018)
The objective of this research was to study the influence of spray drying conditions on the chemical and the physical characteristics of tamarillo powders. The spray drying process was conducted on a mini spray dryer with the use of different carriers that included maltodextrin (MD) and Gum Arabic (AG). The main objective was to determine the effects of drying conditions on colour, water activity, water solubility, hygroscopicity and, size distribution. Moreover, the effects of drying conditions on the total antioxidant activity and total phenolic compounds. The total solid content of tamarillo juices was approximately 9.6% and mixed with different carriers followed by homogenisation. The tamarillo pulp with 3% MD was spray dried at different inlet temperatures from 100 °C to 140 °C. The different feed solution comprised of control, 1.5% MD plus 1.5% AG, 2% MD plus 1% AG, 1% MD plus 2% AG, 3% MD and 3% AG were processed at 120 °C drying air temperature. Aspiration, flow rate and air flow were kept constant at 35 m3/h, 4.79g/min and at 0.6 m3/h respectively. After carrying out this experiment, the highest yield was produced at an inlet temperature of 120 °C. The properties of tamarillo powders produced were analyzed. A significant increase in L* value occurred at 140 °C, whereas the a* value showed a significant decrease. The b* value increased significantly at 130 °C compared to 100 °C and 110 °C. In terms of different carriers used, L* value and b* values were significantly higher than control sample. Water activity value of tamarillo powders was at its least (0.14) when dried at an inlet temperature of 130 °C, and with the incorporation of 1.5% maltodextrin and Gum Arabic. The solubility of tamarillo powders was significantly increased when spray dried using an inlet air temperature of 140 °C compared to 100 °C. Solubility also significantly increased with the use of 3% MD, 1% AG and 2% MD, and 1.5% MD and 1.5% AG, compared to control sample. tamarillo powders treated at different drying temperature and incorporated with different carriers had no significant changes on bulk density and hygroscopicity. The observed surface of tamarillo particles by scanning electron microscopy illustrated a higher degree of agglomeration and cracks in the control sample compared to powders produced using carriers (3% AG, 3% MD, and a 1.5:1.5 MD and AG mixture). The antioxidant activity of hydrophilic compound for CUPRIC assay was significantly increased (p < 0.0001) as the inlet air temperature increased. A significant decrease was found with the hydrophobic antioxidant compound assay using FRAP when inlet air temperature increases. Additionally, freeze dried tamarillo powders had significantly higher antioxidant activities compared to spray dried samples using the CUPRIC, FRAP and Folin-Ciocalteu assays. There was a significant decrease in antioxidant activity with the CUPRIC assay for all tamarillo powder samples encapsulated with carriers compared to control. For FRAP analysis, the antioxidant activity of MD-containing sample was significantly higher than other samples treated with different carriers. In terms of the total phenolic compound, a significant decrease was observed with the use of 3% MD, and mixtures of 1.5% AG and 1.5% MD, 1% AG and 2% MD, and 2% MD and 1% AG, compared to control sample.
Keywords: Tamarillo powder; Drying temperature; Carrier agents; Colour; Water activity; WSI; SEM; Antioxidant activity; TPC